Under pressure: Romania's labour market review. Landmarks of labour shortages - Luminita Chivu; George Georgescu; Alina Bratiloveanu; Irina Bancescu (Romanian Academy, National Institute for Economic Research, 2020)
In recent years, the labour market in Romania became more and more tense, with growing labour shortages affecting the development of many important sectors. This paper is focusing on the labour market imbalances, specifying the main landmarks of labour shortages and highlighting their conditions of emergence and the generating factors for each type of their manifestation. Even if some imbalances has been reported long before, the existence and persistence of quantitative and qualitative labour shortages in Romania became obvious only recently, also under the circumstances of the warning signals of academia and business environment. Among the causes of this growing labour shortages and mismatches are the unfavourable demographic trends, the massive external migration of the skilled and high skilled labour force, the low level of the participation rate, the high inactivity rate, the quantitative and qualitative discrepancies between the supply of the education system and the real needs of the labour market, the size of undeclared work that continues to distort the labour market, the lack of cooperation between employers and institutions with responsibilities in the field employment and professional training of adults. The case study conducted on the IT&C sector, a growing sector in Romania, led to the conclusion that, despite its was claimed by the decision makers as strategic priority, the labour shortages in the sector remains high, being likely to maintain in the near future in the absence of promoting adequate support measures. Under the circumstances of Coronavirus global outbreak early 2020, the effects on the labour market in Romania are difficult to predict, the quantitative and qualitative shortages alleviation depending on the ability of the authorities to manage the crisis and to find the right responses, including by redirecting the returned migrant workers towards the domestic labour market.
Keywords: E60; F22; F66; I20; J08; J10; J21; J23; J61; 330; demographic demographic trends; population aging; emigration; demographic and economic dependency ratio; labour market demand and supply; labour market tensions; internal mobility; labour shortages